Proteases as Markers for Differentiation of Pathogenic and Nonpathogenic Species of Acanthamoeba - Khan, Naveed A. (American Society for Microbiology, 2000)
Acanthamoeba keratitis is a vision-threatening infection caused by pathogenic species of the genus Acanthamoeba. Although not all Acanthamoeba spp. can cause keratitis, it is important to differentiate pathogenic species and isolates from nonpathogens. Since extracellular proteases may play a role in ocular pathology, we used colorimetric, cytopathic, and zymographic assays to assess extracellular protease activity in pathogenic and nonpathogenic Acanthamoeba. Colorimetric assays, using azo-linked protein as a substrate, showed extracellular protease activity in Acanthamoeba-conditioned medium and differentiated pathogenic and nonpathogenic Acanthamoeba. Monolayers of immortalized corneal epithelial cells in four-well plates were used for cytopathic effect (CPE) assays. Pathogenic Acanthamoeba isolates exhibited marked CPE on immortalized corneal epithelial cells, while nonpathogenic isolates did not exhibit CPE. Protease zymography was performed with Acanthamoeba-conditioned medium as well as with Acanthamoeba- plus epithelial-cell-conditioned medium. The zymographic protease assays showed various banding patterns for different strains of Acanthamoeba. In pathogenic Acanthamoeba isolates, all protease bands were inhibited by phenylmethylsulfonyl fluoride (PMSF), suggesting serine type proteases, while in nonpathogenic strains only partial inhibition was observed by using PMSF. The pathogenic Acanthamoeba strains grown under typical laboratory conditions without epithelial cells exhibited one overexpressed protease band of 107 kDa in common; this protease was not observed in nonpathogenic Acanthamoeba strains. The 107-kDa protease exhibited activity over a pH range of 5 to 9.5.